Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. Agile Management system role in achieving the development and creativity of employees in Industrial companies in Jordan: A field study on workers in industrial companies - Jordan 2023Musab Abdullah Ali Alrawajfa, Safaa Mahmoud Bashir Al-Sarayrah2. Legal adaptation of Palestinian resistance in the Gaza Strip In the light of the rules of public international lawMohamad Mahmoud Doughan3. The impact of entrepreneurial awareness on small and medium enterprises  in the light of the requirements of the national transformation programNajwa Samran Awad Alhathli4. Governance of Endowment Institutions and Their Role in Supporting Entrepreneurial Projects  in the Sultanate of Oman "An Analytical Comparative Study"Khalifa Mohammed Khalifa Al-Hamdi5. Determinants of women's participation in the labor force in the Arab countries - an econometric study using the Panel Data model during the period )2000-2020 (Fatimah Fahd Alateeg, Vivian Mohammed Nasrulddin6. The impact of organizational silence on job creativity: A field study for employees of the Ministry of National Guard: in the western sector in Jeddah GovernorateSAEED AYIDH Alahmari, Dr. Kamal Nawawi Tawheed Filemban7. The Impacts of Using Artificial intelligence on Auditors Performance in Saudi Business EnvironmentMs. Kawthar Ali Al-Salem8. Effectiveness of Strategic Planning on Developing Performance in Sudanese Higher Education Institutions from Total Quality Perspective: (Case Study Sudan University of Science and Technology)Dr.Siham Haider Elderderi, Dr.Mohamed  Ahmed Albadawi, Dr. Sameh Mohamed Abdelhay
Keywords: Journal of Economic, Administrative and Legal Sciences